If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (17b + -5) + -8(2b + 1) = -2 Reorder the terms: (-5 + 17b) + -8(2b + 1) = -2 Remove parenthesis around (-5 + 17b) -5 + 17b + -8(2b + 1) = -2 Reorder the terms: -5 + 17b + -8(1 + 2b) = -2 -5 + 17b + (1 * -8 + 2b * -8) = -2 -5 + 17b + (-8 + -16b) = -2 Reorder the terms: -5 + -8 + 17b + -16b = -2 Combine like terms: -5 + -8 = -13 -13 + 17b + -16b = -2 Combine like terms: 17b + -16b = 1b -13 + 1b = -2 Solving -13 + 1b = -2 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 1b = -2 + 13 Combine like terms: -13 + 13 = 0 0 + 1b = -2 + 13 1b = -2 + 13 Combine like terms: -2 + 13 = 11 1b = 11 Divide each side by '1'. b = 11 Simplifying b = 11
| -5+6x=13 | | 10(v+4)-4v=3(2v+2)-7 | | 2x^2-14x+25=0 | | 10+5x=-3x+26 | | -3+(-3)= | | 3x^2+18xy^2=0 | | 9-y=1.5x | | x^2+18x+31= | | 20x^2-x-8=0 | | y^3-14y^2+45= | | 4(2a-3)=28 | | n+.5n=54 | | (x^2-5)(x^2-7x+12)=0 | | 4(2a-3)=283 | | 9x+6x=-60 | | -5(a-6)=-45 | | 10+6m-4=36 | | 8+3x=25 | | (14-2)180=2,520 | | 3(x-2)=2(x+5)-7 | | (16-2)180=2,880 | | 15x-2=58 | | (1/3)+4x=(3x/6)-(4/8) | | 13b^3+9b^2+7b-1=0 | | (12-2)180=2,160 | | 5-16x=69 | | 5*4=20 | | -10+x/3=-12 | | 10x+4=-4x^2 | | -7x+4=18 | | 3y/4-y/2=5 | | -39+4r=-5(5r+2) |